Practical application of matching algorithms in case of a task allocation problem - Szikora, Péter (Serbian Journal of Management, 2015)
Conflicts between individuals or even groups of people are part of everyday social life. However, when handling conflict situations successfully, conflicts are actually solved. In order to achieve such resolution, parties should separate the conflict from the involved people and try to create a cooperative, nonzero-sum mind set concentrating on interests and not on positions agreeing on principles like using a fair standard and a fair procedure. In present paper such impartial standards and procedures - namely matching theory algorithms - that concentrate on factual controversies are introduced.